Transmission of artemisinin-resistant malaria parasites to mosquitoes under antimalarial drug pressure - Witmer,K; Dahalan,F; Delves,M; Yahiya,S; Watson,O; Straschil,U; Chiwcharoen,D; Sorboon,B; Pukrittayakamee,S; Pearson,R; Howick,V; Lawniczak,M; et al. (Antimicrobial Agents and Chemotherapy, 2021)
Resistance to artemisinin-based combination therapy (ACT) in the Plasmodium falciparum parasite is threatening to reverse recent gains in reducing global deaths from malaria. Whilst resistance manifests as delayed parasite clearance in patients the phenotype can only spread geographically via the sexual stages and mosquito transmission. In addition to their asexual killing properties, artemisinin and its derivatives sterilise sexual male gametocytes. Whether resistant parasites overcome this sterilising effect has not, however, been fully tested. Here, we analysed P. falciparum clinical isolates from the Greater Mekong Subregion, each demonstrating delayed clinical clearance and known resistance-associated polymorphisms in Kelch13 (PfK13var). As well as demonstrating reduced asexual sensitivity to drug, certain PfK13var isolates demonstrated a marked reduction in sensitivity to artemisinin in an in vitro male gamete formation assay. Importantly, this same reduction in sensitivity was observed when the most resistant isolate was tested directly in mosquito feeds. These results indicate that, under artemisinin drug pressure, whilst sensitive parasites are blocked, resistant parasites continue transmission. This selective advantage for resistance transmission could favour acquisition of additional host-specificity or polymorphisms affecting partner drug sensitivity in mixed infections. Favoured resistance transmission under ACT coverage could have profound implications for the spread of multidrug resistant malaria beyond Southeast Asia.